Use of english - Jones, Leo (Trẻ, 1996)
Use of English is for intermediate and upper-intermediate students of English who need further revision and practice of the major problem areas of English grammar. The emphasis is on grammar in action: the activities stimulate students into using the grammar they have learned for the purpose of communication.